Pheochromocytomas and Paragangliomas as Causes of Endocrine Hypertension - Canu, Letizia; Parenti, Gabriele; De Filpo, Giuseppina; Mannelli, Massimo (Frontiers in Endocrinology, 2019)
Chromaffin tumors are included among the causes of secondary hypertension because of the release of catecholamines. Nevertheless, the clinical, cardiovascular, and hypertensive picture of patients affected by pheochromocytomas/paragangliomas (PPGL) is extremely variable, due to the different quantitative and qualitative releasing activity of these tumors. A consistent percentage of these patients, about 20%, is normotensive and not affected by the characteristic symptomatic crises due to sudden release of catecholamines. The factors causing such wide clinical variability are many and probably not all known. It is well known that many of these tumors are genetically determined and that the genetic profile influences the biochemical characteristics and the biology of the tumors as well as the clinical presentation of the affected patients. The number of asymptomatic or poorly symptomatic patients is increased after the introduction of genetic screening and the early diagnosis in mutation carriers. In this paper we can review the genotype-phenotype correlation of PPGLs with a focus on the cardiovascular picture.